ACCOUNTING PROBLEMS OF THE FLORIDA REAL ESTATE BOOM. - Boyd, Orton W. (The Accounting Review, 1926)
Abstract The meteoric rise of the 1925 Florida real estate boom, with its great volume and complexity of real estate transactions, forced the practicing public accountants in the state to adopt many changes and variations in the methods usually employed in the accounting for such types of business activity. In the more stabilized or settled sections of the country the purchase or sale of real estate is a rare or extraordinary event in the history of the average individual or firm. Individual purchases or builds a home, which may require years of sacrifice or self-denial to pay for completely. The typical business concern acquires land only for immediate or future use as a business site. Land or buildings used for productive purposes do not change hands rapidly. Even in the case of the purchase of real estate for speculative purposes the turnover is not great, as rapid price increases making possible a quick profit through re-sale are not regularly experienced. In other words, no great number of real estate transactions need be recorded in books of account of the typical business concern in most sections. In most instances one land account and one building account suffice. The rules of debit and credit laid down for such accounts contemplate the use of the real estate solely for productive or investment purposes.